Preparation method of ultraviolet curing antistatic coating with phase separation characteristic

By modifying the surface of the carbon nanotube and using ultraviolet light to separate it from the resin and diluent, an anti-static coating with a clustered grid of carbon nanotubes is formed, which solves the problem of insufficient conductivity of carbon nanotubes in the prior art, and achieves efficient anti-static performance and electrical conductivity improvement.

CN119505588AInactive Publication Date: 2025-02-25ZHEJIANG NAKO NANO NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510080476.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing anti-static technology of carbon nanotube composite coating, the coating formed by uniformly mixing the carbon nanotubes and resin lacks good conductive contact between the carbon nanotubes, resulting in insufficient conductivity, requiring a large amount or thickness to achieve the required conductivity, which increases the cost and is not suitable for thin film applications.

Method used

By adding photosensitivity groups on the surface of the carbon nanotube, the photosensitive groups are converted into polar groups by irradiation with ultraviolet light to form modified carbon nanotubes. Then, during the coating formation process, the drying conditions are controlled to retain the diluent, and ultraviolet irradiation is carried out to separate the carbon nanotubes from the resin and diluent, which promotes the carbon nanotubes to form a cluster network, and finally forms an anti-static coating with a tendency to phase separation and distribution.

Benefits of technology

Through phase separation and clustering of carbon nanotubes, the antistatic properties and conductivity are significantly improved, the amount of carbon nanotubes or the film layer thickness is reduced, the cost is reduced, and the toughness of the film is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505588A_ABST
    Figure CN119505588A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultraviolet curing antistatic coating with a phase separation characteristic. The preparation method comprises the following steps: providing an antistatic coating which comprises a prepolymer, an ultraviolet initiator, a modified carbon nanotube and a diluent; the surface of the modified carbon nanotube is provided with a plurality of non-polar photosensitive groups, when the photosensitive groups are irradiated by ultraviolet light, the photosensitive groups are converted into polar groups, and the diluent is a non-polar system; a liquid layer is formed through coating, a precursor layer is formed through drying, and the diluent still exists in the precursor layer; performing ultraviolet irradiation to cure the prepolymer into a film, and synchronously converting the surface polarity state of the modified carbon nanotube; and thoroughly removing the diluent to obtain the ultraviolet curing antistatic coating. According to the antistatic coating, under the condition of the same amount of the carbon nanotubes, as the carbon nanotubes are bundled to form a net, the conduction resistance between the carbon nanotubes is greatly reduced to form a smooth conduction network, so that the antistatic performance can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antistatic coatings, in particular to a method for preparing an ultraviolet-cured antistatic coating with phase separation characteristics. Background Art

[0002] ‌Anti-static‌ refers to taking a series of measures to prevent the generation and accumulation of static electricity, so as to reduce the harm caused by static electricity to equipment and personnel. Especially in electronic products, static electricity may pose a great threat to precision chips and sensor devices, and the demand for anti-static of various electronic products is very strong.

[0003] Low-cost and effective electrostatic protection can be achieved by setting a conductive coating at the corresponding position of the outer shell or internal circuit board. Therefore, with the gradual development of electronic technology, anti-static coating technology has also developed and progressed.

[0004] As a typical inorganic conductive material, carbon nanotubes have gradually shown excellent application prospects in the field of antistatic. However, the current traditional carbon nanotube composite coating antistatic technology is usually homogeneously dispersed. Figure 1 As shown, in the current technical solutions for making cured antistatic films using carbon nanotubes, carbon nanotubes are usually uniformly mixed (dispersed) with UV curing or heat curing resins to form a coating, and then the coating is coated and cured to form an antistatic coating. In these typical technical solutions, carbon nanotubes and resins are uniformly compounded, which is equivalent to carbon nanotubes "dispersed" in the cured resin phase to form a solid dispersion system. There is usually a certain distance between carbon nanotubes, and there is no good conductive contact between adjacent carbon nanotubes. Although a certain antistatic effect has been achieved, in order to achieve the required conductivity, the amount of carbon nanotubes used is often large, or the thickness of the coating needs to be thick, which not only increases the cost but is also not conducive to application in some scenarios where the coating thickness is thin and the conductivity requirement is high. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a UV-curable antistatic coating with phase separation characteristics to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a UV-curable antistatic coating with phase separation characteristics, comprising: (1) Providing an antistatic coating, wherein the antistatic coating comprises a prepolymer, an ultraviolet initiator, a modified carbon nanotube and a diluent; the surface of the modified carbon nanotube has a plurality of non-polar photosensitive groups, when the photosensitive groups are irradiated by ultraviolet light, the photosensitive groups are converted into polar groups, and the diluent is a non-polar system; (2) coating with the antistatic coating to form a liquid layer, and drying the liquid layer to form a precursor layer, and controlling the drying conditions so that the diluent still exists in the precursor layer; (3) irradiating the precursor layer with ultraviolet light to cure the prepolymer into a film, and simultaneously changing the polarity state of the surface of the modified carbon nanotubes to cause phase separation between the carbon nanotubes, the prepolymer and the diluent; (4) The diluent is completely removed to obtain a UV-curable antistatic coating.

[0007] Furthermore, the photosensitive group in step (1) includes a connecting functional group, an intermediate functional group and a non-polar functional group arranged in sequence in a direction away from the carbon nanotube; the intermediate functional group has a chemical bond that can be decomposed by ultraviolet light.

[0008] Further, the linking functional group includes any one or a combination of two or more of an ester group, an amide group, an amine group, and a sulfonate group; and / or, the intermediate functional group comprises a dimethoxy group and / or a disecondary amino group; And / or, the non-polar functional group includes any one or a combination of two or more of an aromatic group, a C4-C8 alkyl group, an olefin group, and an alkynyl group.

[0009] Furthermore, the connecting functional group, the intermediate functional group and the non-polar functional group are interconnected via an alkyl chain having 1 to 5 carbon atoms.

[0010] Furthermore, the prepolymer in step (1) includes any one or a combination of two or more of acrylate prepolymer, isocyanate prepolymer, epoxy prepolymer, and polyol prepolymer; And / or, the diluent includes any one or a combination of two or more of carbon tetrachloride, benzene, toluene, xylene, ether, and hydroxypropyl acrylate.

[0011] Furthermore, in step (1), the antistatic coating contains 5-10 parts of modified carbon nanotubes, 20-60 parts of prepolymer, 20-50 parts of diluent, and 3-7 parts of photoinitiator, by weight.

[0012] Furthermore, selected additives are added to the antistatic coating, and the selected additives include a leveling agent, a defoaming agent, a wetting agent, and a dispersant that can be added or not added. When the dispersant is added, the mass fraction of the dispersant is below 0.5%.

[0013] Furthermore, the drying condition in step (2) is drying at 80-120° C. for 0.5-1 min.

[0014] Furthermore, the antistatic coating includes a resin matrix and carbon nanotubes embedded in the resin matrix, and a plurality of the carbon nanotubes have a distribution trend of regional clustering and concentration.

[0015] Furthermore, an embodiment of the present invention also provides application of the above antistatic coating in the field of antistatic of electronic products.

[0016] In a first aspect, the present invention provides a method for preparing a UV-curable antistatic coating having phase separation characteristics, comprising: An antistatic coating is provided, wherein the antistatic coating comprises a prepolymer, an ultraviolet initiator, a modified carbon nanotube and a diluent; the surface of the modified carbon nanotube has a plurality of non-polar photosensitive groups, when the photosensitive groups are irradiated by ultraviolet light, the photosensitive groups are converted into polar groups, and the diluent is a non-polar system; Using the antistatic coating to form a liquid layer for coating, and drying the liquid layer to form a precursor layer, and controlling the drying conditions so that the diluent still exists in the precursor layer; The precursor layer is irradiated with ultraviolet light to cure the prepolymer into a film, and the surface polarity state of the modified carbon nanotubes is simultaneously changed to cause phase separation between the carbon nanotubes, the prepolymer and the diluent; The diluent is completely removed to obtain a UV-curable antistatic coating.

[0017] In a second aspect, the present invention further provides an antistatic coating obtained by the above-mentioned preparation method, characterized in that the antistatic coating comprises a resin matrix and carbon nanotubes embedded in the resin matrix, and a plurality of the carbon nanotubes have a distribution trend of regional clustering and concentration.

[0018] In a third aspect, the present invention also provides application of the above antistatic coating in the field of antistatic of electronic products.

[0019] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include: The preparation method provided by the present invention modifies the surface of carbon nanotubes so that the surface has photosensitive groups for photosensitive polarity conversion, and in the process of coating formation, the coating is irradiated with ultraviolet light at a suitable time when the coating is not completely dried and the diluent is removed, so that the surface of the carbon nanotubes changes from the polar state of affinity prepolymer and diluent to the non-polar state of non-affinity, and the carbon nanotubes are pushed to approach each other and cluster, and finally solidify and form an antistatic coating with a phase separation distribution trend after being completely dried; With the same amount of carbon nanotubes, the antistatic coating can show a very obvious improvement in antistatic performance because the carbon nanotubes are bundled into a network, and the conduction resistance between the carbon nanotubes is greatly reduced to form a smooth conduction network; in addition, because the carbon nanotubes are bundled into a network, the van der Waals interaction between the tubes is enhanced, which also helps to improve the toughness of the film to a certain extent.

[0020] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 It is a schematic diagram of the microstructure of an existing antistatic coating provided by a background technology of the present invention; Figure 2 Schematic diagram of the microstructure of an antistatic coating provided by a typical embodiment of the present invention; Figure 3 It is a schematic diagram of the ultraviolet light polarity change process provided by a typical implementation case of the present invention. DETAILED DESCRIPTION

[0022] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0024] The embodiment of the present invention provides a method for preparing a UV-curable antistatic coating having phase separation characteristics, which comprises the following steps: An antistatic coating is provided, wherein the antistatic coating comprises a prepolymer, an ultraviolet initiator, a modified carbon nanotube and a diluent; the surface of the modified carbon nanotube has a plurality of non-polar photosensitive groups, when the photosensitive groups are irradiated by ultraviolet light, the photosensitive groups are converted into polar groups, and the diluent is a non-polar system; Using the antistatic coating to form a liquid layer for coating, and drying the liquid layer to form a precursor layer, and controlling the drying conditions so that the diluent still exists in the precursor layer; The precursor layer is irradiated with ultraviolet light to cure the prepolymer into a film, and the surface polarity state of the modified carbon nanotubes is simultaneously changed to cause phase separation between the carbon nanotubes, the prepolymer and the diluent; The diluent is completely removed to obtain a UV-curable antistatic coating.

[0025] like Figure 2 As shown, in the above technical scheme, when the coating is applied to form a liquid film and after a certain degree of drying, the precursor film is irradiated with ultraviolet light to initiate a curing reaction. Synchronously, the polarity of the carbon nanotube surface changes, and the carbon nanotube changes from solvent affinity to solvent repulsion (relative), so that the carbon nanotubes have a tendency to agglomerate in the system, but will not form a very strong phase separation phenomenon to cause film stratification or dispersion, so as to avoid affecting film formation; the repulsiveness is used to squeeze and aggregate multiple carbon nanotubes to form a mutually combined conductive network skeleton, which is gradually fixed in the cured resin to form an antistatic coating composed of a carbon nanotube aggregation network and a cured resin.

[0026] A key implementation detail of the above technical solution is that the phase separation transformation must be carried out simultaneously with the film curing. If it is too early, the coating will be delaminated and precipitated, and the film cannot be formed (for example, if the initiator is a thermal curing system, the ultraviolet polarity transformation and thermal curing are not carried out simultaneously); if it is too late, the carbon nanotubes have already been cured and cannot be pushed or offset. Therefore, the present invention uses the synergistic cooperation of photocuring + photochemical conversion to achieve the above purpose, and it is difficult to achieve synchronization by other methods.

[0027] In addition, the timing of achieving UV conversion and curing is also critical. If it is carried out just after coating to form a liquid layer, the fluidity of the liquid layer is too large. Even if phase separation occurs, the separation effect will be too strong due to the excessive fluidity, causing obvious separation of the carbon nanotubes and the resin system, resulting in difficulty in film formation. If the light is exposed too late, for example, referring to the traditional film-forming method, light curing is carried out after the solvent has almost evaporated, then due to the lack of fluidity, the carbon nanotubes can be regarded as large molecules with a large scale and weak diffusion ability. Therefore, even if functional group rejection occurs at this time, the formation of a cluster network cannot be achieved.

[0028] The inventor of the present invention has previously proposed a carbon nanotube antistatic coating that uses an emulsion method to configure an aqueous dispersion system containing oily droplets. After coating and curing, the original film is subjected to organic extraction to remove the oily components therein to form a porous, carbon nanotube-bundled conductive film layer structure. However, this technical solution, on the one hand, requires an additional extraction process, which is difficult to achieve during film preparation or coating application; on the other hand, there must be a pore structure inside the film left behind by the oily components detaching from the film, which reduces the film density and inevitably has natural disadvantages in terms of strength and conductivity.

[0029] The present invention continues the research based on the above technical ideas, and creatively adopts the technical means of polarity control to achieve spontaneous phase separation, aggregation and networking of carbon nanotubes, avoiding the later extraction process, and the formed film layer is dense and tight, which is obviously better than the technical solution proposed by the inventor of the present invention.

[0030] As for the selection of specific modifying agents, in some embodiments, the photosensitive group includes a connecting functional group, an intermediate functional group and a non-polar functional group arranged in sequence in a direction away from the carbon nanotube; the intermediate functional group has a chemical bond that can be decomposed by ultraviolet light.

[0031] In some more specific embodiments, the connecting functional group includes any one of ester group, amide group, amino group, sulfonate group or a combination of two or more thereof, but is not limited thereto. Various groups that can be connected to the surface of carbon nanotubes are within the scope of consideration.

[0032] Furthermore, in some embodiments, the intermediate functional group comprises a dimethoxy group and / or a di-secondary amino group, which are common double electron-donating groups and can be irradiated with ultraviolet light.

[0033] In some embodiments, the non-polar functional group includes any one or a combination of two or more of an aromatic group, a C4-C8 alkyl group, an alkene group, and an alkyne group.

[0034] In some embodiments, the connecting functional group, the intermediate functional group and the non-polar functional group are connected to each other through an alkyl chain having 1 to 5 carbon atoms.

[0035] As some typical examples, the structure of the photosensitive group is Figure 3 As shown, R1 represents the connecting group, and its main function is to connect the surface of the carbon nanotube and other groups. The usual technical route is to react and connect the carbon nanotubes with surface functionalization (such as hydroxylation or carboxylation, etc.) through chemical reactions, for example, ester groups, amide groups, and even chemical bonds such as peptide bonds and hydrogen bonds can be formed to achieve functional connection; R2 represents an intermediate group, which can also be called a photolysis group in some existing literature. Its main function is to undergo photolysis reaction under the excitation of ultraviolet light, for example, a dimethoxy group forms an -OH group under photolysis; R3 is a typical non-polar group, such as a benzene ring or a long alkyl chain, a cycloalkyl group, etc., which will be removed during the photolysis reaction and lose the ability to maintain the non-polarity of the surface.

[0036] In addition, regarding other components, in some embodiments, the prepolymer includes any one or a combination of two or more of acrylate prepolymers, isocyanate prepolymers, epoxy prepolymers, and polyol prepolymers, but is not limited thereto. Thermosetting resin prepolymers that can be dissolved in non-polar solvents such as toluene and xylene are included in this list.

[0037] Regarding the diluent, in some embodiments, the optional range of the diluent includes any one or a combination of two or more of carbon tetrachloride, benzene, toluene, xylene, ethyl ether, and hydroxypropyl acrylate, but is not limited thereto. In theory, any solvent with non-polar properties that is compatible with the above-mentioned resin system can be used.

[0038] Regarding specific component ratios, in some embodiments, the antistatic coating contains 5-10 parts of modified carbon nanotubes, 20-60 parts of prepolymers, 20-50 parts of diluents, and 3-7 parts of photoinitiators, by weight. Of course, the above ratio range is a commonly used range for experiments in the present invention, and does not mean that the purpose of the present invention cannot be achieved beyond this range.

[0039] In addition, in some embodiments, selected additives are added to the antistatic coating, and the selected additives include a leveling agent, a defoaming agent, a wetting agent, and a dispersant that can be added or not added. When the dispersant is added, the mass fraction of the dispersant is below 0.5%.

[0040] In the above technical solution, even if a dispersant is added, the amount of the dispersant added must be careful not to be too large. This is because the function of the dispersant is to disperse insoluble solid substances in the liquid medium. If the amount of the dispersant added is too large, the dispersion ability of the carbon nanotubes will be significantly improved, masking the phase separation trend caused by the polarity change, thereby failing to achieve the corresponding purpose.

[0041] And, in some embodiments, in order to retain a portion of the diluent, the drying conditions include drying at 80-120°C for 0.5-1 min. The drying temperature and drying time should not be too high or too long, otherwise it is difficult to control the degree of diluent retention. Of course, even if the above drying conditions are not adopted, for example, natural drying can be performed, the time needs to be controlled to avoid excessive volatilization of the diluent. It is usually acceptable to control the volatilization ratio of the diluent to be within the range of 30-70% (the volatilization amount of the diluent can be measured by weighing and compared with the original amount of the diluent).

[0042] The embodiment of the present invention further provides an antistatic coating obtained by the above preparation method, wherein the antistatic coating comprises a resin matrix and carbon nanotubes embedded in the resin matrix, wherein a plurality of the carbon nanotubes have a distribution trend of regional clustering and concentration.

[0043] Furthermore, the embodiments of the present invention also provide the application of the above antistatic coating in the field of antistatic of electronic products.

[0044] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] Embodiment 1: This embodiment first provides an antistatic coating and the preparation and coating process of the coating, which are specifically as follows: (1) Disperse 10 parts of hydroxylated carbon nanotube powder in 40 parts of ethanol with an appropriate amount of dispersant, and then add 1 part of Figure 3 The compound shown (wherein the value of n is 2) and an appropriate amount of acid are heated under reflux for 5 hours; (2) neutralizing the solution, filtering it, washing it with deionized water for 3 times, and drying it at room temperature for 3 hours to obtain modified carbon nanotubes; of course, the specific acquisition of modified carbon nanotubes is not limited to the method of connecting by esterification reaction as illustrated in this embodiment. Functionalization such as oxidation and acidification on the surface of carbon nanotubes and then using chemical reactions to achieve reaction connection, or using coupling agents to connect or ligand coordination / exchange to achieve surface modification of molecules with photodecomposition polarity change characteristics can achieve equivalent effects, and the functionalization reagent is not limited to Figure 3 The specific molecular structures shown can achieve these functions by obtaining molecules of corresponding structures through commercial purchase or commissioned synthesis; (3) 5 parts of the modified carbon nanotubes, 30 parts of UV prepolymer A (Songda New Materials (a mixed solvent of isobornyl acrylate and toluene in a ratio of 1:1), 0.3 parts of leveling agent BYK-333, and 3 parts of photoinitiator (ITX and TPO in a ratio of 3:1) were stirred at 120 rpm for 20 min and uniformly mixed, and then fully ground into a slurry using a grinder to obtain an antistatic coating; (4) The antistatic coating is coated on a carrier sheet with a coating thickness of about 80 μm, and then dried in an oven at 100°C for 0.5 min. At this time, the weight loss of the film is about 50% of the volatilization of the diluent. When the film is in a semi-dry state, it is irradiated with a UV lamp with a power density generally controlled at 10-15 W / m 2The irradiation time is 60 minutes to ensure the effect. The irradiation time can also be extended, which basically will not bring adverse consequences, mainly losing process time; then continue to dry or dry naturally to finally obtain an antistatic coating.

[0047] The sheet resistance and bonding strength / toughness tests of the film obtained in this embodiment showed that the sheet resistance was 3.8-4.5×10 3 Ω / sq; Adhesion / toughness tests include tape peeling test and grid test (10*10, interval 1mm), and no shedding was found in the test results.

[0048] Example 2: This example is generally the same as Example 1, with the main difference being that the same modified carbon nanotubes as in Example 1 are used, with the addition amount adjusted to 10 parts, the prepolymer includes 15 parts of UV prepolymer A (Songda New Material SD-1326B), 15 parts of UV prepolymer B (Sanqi New Material L-6604), the active diluent is a mixed solvent of 20 parts of isobornyl acrylate and 1:1 of xylene, and the photoinitiator is 7 parts of TPO.

[0049] This embodiment can still obtain an antistatic coating with better antistatic performance and bonding strength / toughness.

[0050] Example 3: This example is generally the same as Example 1, with the main difference being that: the same modified carbon nanotubes as in Example 1 are used, and the addition amount thereof is adjusted to 7 parts, the prepolymer includes 20 parts of UV prepolymer A (Songda New Materials SD-1326B), 20 parts of UV prepolymer B (Runao Chemical R-7496), the active diluent is a mixed solvent of 50 parts of isobornyl acrylate and ether in a ratio of 1:1, and the photoinitiator is 5 parts of ITX.

[0051] This embodiment can still obtain an antistatic coating with better antistatic performance and bonding strength / toughness.

[0052] Example 4: This example is substantially the same as Example 1, with the main difference being that the group R3 is replaced by a naphthyl group.

[0053] Still, an antistatic coating with the same properties can be obtained.

[0054] Comparative Example 1: This comparative example is substantially the same as Example 1, except that carbon nanotubes that have not undergone any surface modification are used instead of the modified carbon nanotubes.

[0055] The sheet resistance of the film obtained in this example was tested, and the sheet resistance was 2.5-3.2×10 3 Ω / sq, which was significantly lower than that in Example 1.

[0056] Comparative Example 2: This comparative example is substantially the same as Example 1, except that the drying time is extended to 2 minutes or more so that the film is completely dried before being exposed to ultraviolet light.

[0057] The square resistance of the film was tested, and it was found that its square resistance was close to that of comparative example 1, and was in the range of 2-3×103Ω / sq.

[0058] Comparative Example 3: This comparative example is substantially the same as Example 1, except that the film is exposed to ultraviolet light immediately after coating and then air-dried.

[0059] The film obtained in this comparative example is very easy to fall off or dissociate. When the probe method is used to measure the square resistance, due to the instability of the film structure, it is impossible to achieve stable measurement and obtain an accurate value.

[0060] Comparative Example 4: This comparative example is substantially the same as Example 1, except that the amount of the dispersant is adjusted to 1 part.

[0061] The sheet resistance of the film layer obtained in this comparative example is similar to that of comparative example 1-2, indicating that the excessive addition of dispersant masks the phase separation effect and fails to form a cluster network to optimize the conductive properties.

[0062] Based on the above embodiments and comparative examples, it can be clearly seen that the embodiments of the present invention perform functional modification of the carbon nanotube surface by photosensitive polarity conversion, so that while the resin is cured by ultraviolet light, the chemical environment on the surface of the carbon nanotube is converted to polarity, and the carbon nanotubes are phase-separated to a certain extent from the diluent and the resin by repulsion, and the carbon nanotubes are squeezed and aggregated to form a conductive network and fixed in the cured resin to form a conductive coating; at the same carbon nanotube dosage and film thickness, the conductivity is significantly improved compared to traditional conductive coatings while maintaining mechanical strength; similarly, at the same target square resistance requirement, the amount of expensive single-walled carbon nanotubes can be significantly reduced or the film thickness can be significantly reduced.

[0063] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0064] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a UV-curable antistatic coating having phase separation characteristics, characterized in that: include: (1) Providing an antistatic coating, wherein the antistatic coating comprises a prepolymer, an ultraviolet initiator, a modified carbon nanotube and a diluent; the surface of the modified carbon nanotube has a plurality of non-polar photosensitive groups, when the photosensitive groups are irradiated by ultraviolet light, the photosensitive groups are converted into polar groups, and the diluent is a non-polar system; (2) coating with the antistatic coating to form a liquid layer, and drying the liquid layer to form a precursor layer, and controlling the drying conditions so that the diluent still exists in the precursor layer; (3) irradiating the precursor layer with ultraviolet light to cure the prepolymer into a film, and simultaneously changing the polarity state of the surface of the modified carbon nanotubes to cause phase separation between the carbon nanotubes, the prepolymer and the diluent; (4) The diluent is completely removed to obtain a UV-curable antistatic coating.

2. The method for preparing a UV-curable antistatic coating having phase separation characteristics according to claim 1, characterized in that: The photosensitive group in step (1) includes a connecting functional group, an intermediate functional group and a non-polar functional group which are sequentially arranged in a direction away from the carbon nanotube; the intermediate functional group has a chemical bond that can be decomposed by ultraviolet light.

3. The method for preparing a UV-curable antistatic coating with phase separation characteristics according to claim 2, characterized in that: The connecting functional group includes any one or a combination of two or more of an ester group, an amide group, an amine group, and a sulfonate group; and / or, the intermediate functional group comprises a dimethoxy group and / or a disecondary amino group; And / or, the non-polar functional group includes any one or a combination of two or more of an aromatic group, a C4-C8 alkyl group, an olefin group, and an alkynyl group.

4. The method for preparing a UV-curable antistatic coating having phase separation characteristics according to claim 3, characterized in that: The connecting functional group, the intermediate functional group and the non-polar functional group are connected to each other through an alkyl chain having 1 to 5 carbon atoms.

5. The method for preparing a UV-curable antistatic coating with phase separation characteristics according to claim 1, characterized in that: The prepolymer in step (1) includes any one of acrylate prepolymer, isocyanate prepolymer, epoxy prepolymer, polyol prepolymer or a combination of two or more thereof; And / or, the diluent includes any one or a combination of two or more of carbon tetrachloride, benzene, toluene, xylene, ether, and hydroxypropyl acrylate.

6. The method for preparing a UV-curable antistatic coating with phase separation characteristics according to claim 1, characterized in that: In step (1), the antistatic coating contains 5-10 parts of modified carbon nanotubes, 20-60 parts of prepolymer, 20-50 parts of diluent and 3-7 parts of photoinitiator, by weight.

7. The method for preparing a UV-curable antistatic coating with phase separation characteristics according to claim 6, characterized in that: The antistatic coating is further added with selected additives, which include a leveling agent, a defoaming agent, a wetting agent, and a dispersant which can be added or not added. When the dispersant is added, the mass fraction of the dispersant is below 0.5%.

8. The method for preparing a UV-curable antistatic coating with phase separation characteristics according to claim 1, characterized in that: The drying condition in step (2) is drying at 80-120° C. for 0.5-1 min.

9. The antistatic coating obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The antistatic coating comprises a resin matrix and carbon nanotubes embedded in the resin matrix, and a plurality of the carbon nanotubes have a distribution trend of regional clustering and concentration.

10. Use of the antistatic coating according to claim 9 in the field of antistatic treatment of electronic products.

Citation Information

Patent Citations

  • Preparation method of photosensitive copolymer and carbon nano tube compounded molecularly imprinted sensor

    CN105116033A

  • Ultraviolet curing paint based on carbon nanotubes and preparation method of ultraviolet curing paint

    CN106634089A

  • Photosensitive resin composition and cured film thereof

    CN118244576A

  • Environment-friendly carbon nanotube antistatic agent, coating, composite material and assembly

    CN119060577A

  • Carbon nanotube composite and method of manufacturing the same

    US20160045644A1